ISO 9001 CERTIFIED IMPLEMENTATION IN A CARDBOARD COMPANY. INTERNAL AND EXTERNAL IMPACTS EVALUATION - Vieira, A.; Caraschi, J. C.; Prates, G. A. (Revista Brasileira de Engenharia de Biossistemas, 2014)
This paper presents the evaluation of internal and external impacts of a company that has adopted a system of total quality management: ISO 9001 certified. Based on a case study, supported in parallel bibliographic references from the literature, in a cardboard sector company. The survey aims to measure and evaluate the basic concepts of quality and the benefits of certification. Upon completion of this study it was found that actually getting a certified ISO 9001 brings many organizational impacts and leads to overall improvement of the company, as the management capacity and overall relationships, increase the number of customers and suppliers, improved company image on the market.